Role of the PERK-eIF2α-CHOP Signaling Pathway in the Effect of Needle Knife Therapy on Knee Joint Chondrocyte Apoptosis. (16th June 2019) - Yang, Yong-hui; Liu, Tian-hao; Zhang, Li-da; Chen, Zhu-yue; Huang, Xiao-shuang
Abstract : Needle knife therapy, a form of acupuncture and moxibustion, has been widely used in the clinical treatment of knee osteoarthritis (KOA). However, the mechanism is not clear. Therefore, we studied the mechanisms of action of needle knife intervention on KOA in rabbits, with the PERK-eIF2 α -CHOP pathway as a starting point, in order to determine the mechanism underlying knee joint chondrocyte apoptosis. Apoptosis and ultrastructural changes in the articular cartilage were examined by pathological study and transmission electron microscopy, and PERK, eIF2 α, and CHOP mRNA and protein levels were detected by qRT-PCR and western blot, respectively. PERK, eIF2 α, and CHOP protein levels were significantly higher in the model group than in the normal group ( P < 0.01) and were considerably downregulated in the needle knife and the medicine groups compared to the model group ( P < 0.01). The eIF2 α, p-eIF2 α, and CHOP protein levels were not significantly different between the needle knife and medicine groups. The PERK, eIF2 α, and CHOP mRNA levels in the drug group were higher than those in the needle knife group ( P < 0.01). Needle knife therapy can regulate PERK-eIF2 α -CHOP signaling pathway, which could be one of the mechanisms by which it affects chondrocyte apoptosis in KOA rabbits.